INTEGRALITY IN THE ROUTINES OF PRACTICE IN A PSYCHO-SOCIAL ATTENTION CENTER - Denise Bermudez Pereira; Valéria Cristina Christello Coimbra; Luciane Prado Kantorski; Michele Mandagará de Oliveira; Marilu Correa Soares; Greice Schrader (Universidade Federal do Paraná, 2011)
This descriptive case study with a qualitative approach, carried out in a Center for Psycho-Social Attention in the south of Rio Grande do Sul State in Brazil, aimed to analyze the routine of practices of the healthcare professionals, with the integrality of the organization of practices as its reference. Data was collected via interviews with 21 members of the team and the categories Interaction and construction spaces: integrality in daily practices and Difficulties met in daily workwere identified through thematic analysis. It was verified that the logic of the work is constituted in a user-centred manner; that interaction and construction spaces provide opportunities for integration between team and service users, potentializing the integrality. Despite some difficulties, such as the existence of the mental health clinic in the service, it is concluded that the practices promote integrality, as they suggest new alternatives of care, valuing the human being in suffering.